Analisis Perancangan Model Kebijakan Dalam Mengurangi Emisi Karbon Sektor Energi Di Indonesia Dengan Pendekatan Sistem Dinamis - Rahsya Akbar Muhammad Amin; Dwi Sukma Donoriyanto (Student Scientific Creativity Journal, 2023)
In 2022, Indonesia will host the G20 Summit with one of the goals agreed upon by G20 members is to reduce carbon emissions produced by each G20 country. Therefore, a model design was made to consider the most optimal policy to overcome this. The research uses a dynamic system model, with the process of identifying and defining problems, system conceptualization, model formulation, model simulation, verification and validation of policy analysis models, and policy implementation. The most optimum result is the imposition of a tax per carbon emission on producing sources with an effectiveness of 20%.